# Graph the function  `f(x)=x^3`  and `g(x)=x^3+1.`

To graph the function `f(x)=x^3` , assign values to x and solve for y.

`x=-3`  ,  `y=x^3=(-3)=-27`

`x=-2`  ,  `y=(-2)^3=-8`

`x=-1`  ,  `y=(-1)^3=-1`

`x=0`   ,  `y=0^3=0`

`x=1`   ,  `y=1^3=1`

`x=2`   ,  `y=2^3=8`

`x=3`   ,  `y=3^3=27`

Then, plot the points...

To graph the function `f(x)=x^3` , assign values to x and solve for y.

`x=-3`  ,  `y=x^3=(-3)=-27`

`x=-2`  ,  `y=(-2)^3=-8`

`x=-1`  ,  `y=(-1)^3=-1`

`x=0`   ,  `y=0^3=0`

`x=1`   ,  `y=1^3=1`

`x=2`   ,  `y=2^3=8`

`x=3`   ,  `y=3^3=27`

Then, plot the points (-3,-27) , (-2,-8) , (-1,-1) , (0,0) , (1,1) , (2,8) , (3,27). And connect them.

Hence, the graph of the function `f(x)=x^3` is:

To graph for the second function `g(x)=x^3+1` , notice that we only add the previous function with 1 to get the second function g(x).

So, we may express the second function as:

`g(x)=x^3+1`

`g(x)=f(x) + 1`

Since we already have the graph of f(x),  to graph g(x), apply transformation of function.

Since g(x) is in the form  `y_2 = y_1+k` , do vertical shift. So, move the graph of f(x) 1 unit up to get the graph of g(x).

Thus, the graph of the function `g(x) =x^3+1` is:

Approved by eNotes Editorial Team